1998
DOI: 10.1183/09031936.98.11020278
|View full text |Cite
|
Sign up to set email alerts
|

The Po River Delta Respiratory Epidemiological Survey: an analysis of factors related to level of total serum IgE

Abstract: The purpose of the present study was to analyse whether sex, age, skin test reactivity, cigarette smoking and occupational exposure were related to the total serum immunoglobulin (Ig)E concentrations (kU x L[-1]), in a general population sample. We studied 1,905 subjects (915 males, 990 females) of a general population sample (n=2,841, 8-73 yrs) participating in the second cross-sectional respiratory epidemiological survey in the rural Po Delta area (near Venice, North Italy). Distribution of total serum IgE c… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

8
37
1
2

Year Published

2001
2001
2016
2016

Publication Types

Select...
5
3

Relationship

0
8

Authors

Journals

citations
Cited by 46 publications
(48 citation statements)
references
References 35 publications
(72 reference statements)
8
37
1
2
Order By: Relevance
“…6) In another study, the peak of IgE concentration was noted at age group of 8-14 years. 7) The discriminating ability of TIE is most suitable in children aged 5-16 years according to the results of our study and those of others. 6,7) Serum TIE values decline with age in the general population.…”
Section: Discussionsupporting
confidence: 66%
See 1 more Smart Citation
“…6) In another study, the peak of IgE concentration was noted at age group of 8-14 years. 7) The discriminating ability of TIE is most suitable in children aged 5-16 years according to the results of our study and those of others. 6,7) Serum TIE values decline with age in the general population.…”
Section: Discussionsupporting
confidence: 66%
“…7) The discriminating ability of TIE is most suitable in children aged 5-16 years according to the results of our study and those of others. 6,7) Serum TIE values decline with age in the general population. 8) In our study, the consistency between TIE and the symptoms was found between 51% and 57% in adult age groups.…”
Section: Discussionsupporting
confidence: 66%
“…Among children in the USA, followedup from birth to 4 yrs of age, the major increase was observed before the age of 2 yrs, although total IgE level increased even later [56]. Cross-sectional data suggest that total IgE levels are at their highest in childhood and fall steadily after the age of 15 yrs [16,21,22,61]. Longitudinal data from a 20-yr followup of people living in Tucson, Arizona largely con®rm this.…”
Section: Modi®ers Of Allergy Markersmentioning
confidence: 89%
“…L -1 ). The geometric mean of total serum IgE as well as speci®c serum IgE was lower in Nordic populations [17,18] than in young adults in South Wales [19], adults in Tucson, Arizona [20], in Italy [21] and in the Netherlands [22]. This may partly be due to differences in methods, in mean age of the populations, as well as differences in allergen exposure.…”
Section: Prevalence In Epidemiological Studiesmentioning
confidence: 99%
“…A case-control study demonstrated that self-reported ETS exposure was associated with obstructive respiratory disease, defined as asthma, chronic bronchitis, or emphysema [27]. Reports from the Adventist Health Study of Smog (AHSMOG) indicated a relationship between self-reported ETS exposure and a greater risk of "airway obstructive disease" (asthma, chronic bronchitis, or emphysema), chronic bronchitis symptoms, and airway obstruction by pulmonary function testing [28,29]. These studies are limited by the lack of a comprehensive and specific definition of COPD (i.e., includes chronic bronchitis, emphysema, and COPD but not asthma), the absence of cumulative lifetime ETS exposure data, and the omission of other occupational exposures that could be correlated with ETS exposure.…”
Section: Discussionmentioning
confidence: 99%